2016
DOI: 10.1177/1076217516628568
|View full text |Cite
|
Sign up to set email alerts
|

Using Enrichment Clusters to Address the Needs of Culturally and Linguistically Diverse Learners

Abstract: Using data from teacher interviews, classroom observations, and a professional development workshop, this article explains how one component of the schoolwide enrichment model (SEM) has been implemented at a culturally diverse elementary school serving primarily Latina/o and African American students. Based on a broadened conception of giftedness, the SEM incorporates enrichment clusters, which are designed to expose students to a variety of topics that would not ordinarily be covered in the regular curriculum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…As related to instruction, empirical work has suggested providing students with access to dual or heritage language courses and providing teachers with training that can raise their expectations of GT ELs and help them provide supportive networks for students (Olszewski-Kubilius & Clarenbach, 2014). Regarding curriculum, more empirical work has identified particular intervention efforts and grouping models that resulted in achievement growth for this population (Allen et al, 2016; Brulles et al, 2010, 2012; Cho et al, 2015). Finally, one particular Saturday/summer enrichment program for potentially GT ELs resulted in positive academic experiences for these students with their peers, teachers, and school (Pereira & Gentry, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As related to instruction, empirical work has suggested providing students with access to dual or heritage language courses and providing teachers with training that can raise their expectations of GT ELs and help them provide supportive networks for students (Olszewski-Kubilius & Clarenbach, 2014). Regarding curriculum, more empirical work has identified particular intervention efforts and grouping models that resulted in achievement growth for this population (Allen et al, 2016; Brulles et al, 2010, 2012; Cho et al, 2015). Finally, one particular Saturday/summer enrichment program for potentially GT ELs resulted in positive academic experiences for these students with their peers, teachers, and school (Pereira & Gentry, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Curriculum. Four empirical papers examined the effects of using two different math interventions with ELs through Mentoring Mathematical Minds (M 3 ) curricular units (Cho et al, 2015) and a cluster grouping model (see also Allen et al, 2016;Brulles et al, 2010Brulles et al, , 2012. In the first, M 3 curricular units combine the teaching practices of GT education with the content and process standards of the National Council of Teachers of Mathematics.…”
Section: Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The SEM, with a talent pool identification model, expands exposure to a larger and more diverse group of students and has been used for that purpose and implemented in high poverty, urban and rural schools for decades. For example, Allen at al. (2016) found that use of enrichment clusters at an urban, largely Latinx elementary school improved the school's sense of community, validated students' home cultures, increased attendance, and developed students' sense of agency.…”
Section: Culturally Diverse Populationsmentioning
confidence: 99%
“…Use of Enrichment Triad with students from underrepresented minorities showed increased academic achievement, leadership, and creative skills. Allen et al (2016) 2016 Gifted Child Today Use of enrichment clusters expanded opportunities for CLD students at one urban school.…”
Section: Early Childhood Educationmentioning
confidence: 99%